1999
DOI: 10.1080/00074919912331337507
|View full text |Cite
|
Sign up to set email alerts
|

Parental Education and child Nutrition in Indonesia

Abstract: This study uses 1989 Susenas household data to examine the impact of parental education on pre-school children's nutritional status, as measured by weight-for-age Z-scores. Reduced form regressions are estimated separately for boys and girls in rural and urban areas; explanatory variables include mother's and household head's education; per capita household expenditure; and aspects of the household sanitary environment. The analysis controls for influence of unobserved heterogeneity at village level, e.g. diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
(22 reference statements)
4
26
0
Order By: Relevance
“…Rather, in both boys and girls, nutritional status was most strongly associated with number of teachers in the village, a measure of access to education. This finding is consistent with other international development research showing the importance of education in promoting nutritional health (Bindon and Vitzthum, 2002;Ene-Obong et al, 2001;Mukudi, 2003;Skoufias, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Rather, in both boys and girls, nutritional status was most strongly associated with number of teachers in the village, a measure of access to education. This finding is consistent with other international development research showing the importance of education in promoting nutritional health (Bindon and Vitzthum, 2002;Ene-Obong et al, 2001;Mukudi, 2003;Skoufias, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…While studies on the association between women's empowerment and child nutritional status abound, literature discussing gender differences therein are far fewer. However, the three studies that the authors are aware of, which have studied the gendered link between women's empowerment and child nutritional status, showed interesting findings that require further research (Skoufias, 1999;Khatun et al, 2004;Bose, 2011). Skoufias (1999) studied whether the number of years that the mothers spend in school affects the weight-for-age of under-five children in Indonesia.…”
Section: Women's Empowerment and Child And Adolescent Nutritional Statusmentioning
confidence: 99%
“…Research has also found that, in most cases, both mother's working status and her bargaining power are positively correlated with their children's nutritional status (Toyama et al, 2001;Shroff et al, 2011;Roshita et al, 2013). Several studies have also reported that empowered mothers were able to reduce inequality in nutritional status between boys and girls (Skoufias, 1999;Khatun et al, 2004;Bose, 2011). For example, Bose (2011) showed that Indian mothers with a job were able to provide more protein-rich food to improve the nutrition of their undernourished daughters, thus compensating the existing gender gap.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the human capital embodied in a mother can have a significant impact on a child's health status. [9] More education results in greater knowledge and better access to and processing of information (Thomas, Strauss and Henrique's 1990). In the context that better educated parents are more successful in protecting or improving their children's health status, public health programs intended at reducing child under nutrition and obesity.…”
Section: American Journal Of Sports Science and Medicinementioning
confidence: 99%
“…In the context that better educated parents are more successful in protecting or improving their children's health status, public health programs intended at reducing child under nutrition and obesity. Identifying the significant connection between child health and education of parents is effective to construct a better health policy [9].…”
Section: American Journal Of Sports Science and Medicinementioning
confidence: 99%